Тheoretical aspect of the relationship of tradition and innovation (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the theoretical aspects of the relation of tradition and innovation, the peculiarities of culture. Concept of tradition and innovation can be related to the different layers of human culture, human history. The tradition originated and developed in primitive culture where a certain set of symbols and knowledge handed down from generation to generation, and mastered by all members of the primitive group. While the birth of civilizations as a center in the middle of the primitive peripheral needed something more, namely the emergence of cultural innovation. In order to establish an ongoing process of growth were required to base core on which to build the innovation process. That tradition has become a cultural nucleus on which civilization rests. Because the ﬁ rst civilizations arise as the result of creativity that goes beyond tradition. It is known that the the Strategy of Innovative Industrial Development of Kazakhstan was adopted by Decree of Nursultan Nazarbayev, the President of the Republic of Kazakhstan. Many opinions were uttered and analytical scientiﬁ c research works were done on this issue. Innovative trends in a society are driven by the fast pace of changes in technology and manufacturing equipment. The driving force for these changes is the immensity of information in all the spheres of industrial and social activities. Industrial development and enhancement is fostered by a man, his knowledge, expertise, skills, and creativity. Keywords: culture, tradition, innovation, ethnic culture, civilization, dialogue, customs, values..